Overcoming barriers to exposure by integrating principles derived from ACT (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Exposure-based therapies have a central role in Clinical Behavior Analysis and have repeatedly demonstrated their efficacy in the treatment of a wide array of psychological problems. However, their effectiveness in the clinic has been compromised by a significant percentage of clients who drop out or do not respond to therapy, and by clinicians who fear that exposure therapy is dangerous, intolerable and unethical. It is argued that the integration of behavioral principles not commonly emphasized in exposure-based therapies, derived from Acceptance and Commitment Therapy (ACT), may contribute in reducing the effectiveness obstacles found, and consequently optimize the implementation of exposure. The paper’s objective is to present such integration through a brief illustration of two clinical cases, one with symptoms compatible with Obsessive-Compulsive Disorder and the other with Specific Phobia. It is argued that the proposed integration may reduce client’s and therapist’s avoidance of exposure and broaden the client’s repertoire when faced with the feared event.
Keywords: exposure; acceptance and commitment therapy; effectiveness